THE EFFECT OF CARRAGEENAN AND LEMON RATIO ON ANTIOXIDANT ACTIVITY AND PHYSICAL PROPERTIES OF JELLY BUTTERFLY PEA - Titi Mutiara Kiranawati; Rina Rifqie Mariana; Nindry Efrinasari (BPFP Faperta UNIB, 2022)
Plant-derived pigments are becoming increasingly important globally as a potential source of biocolours for their versatility and avoiding the health hazards caused by synthetic colours. The use of additives such as preservatives, artificial flavours, and artificial coloring can cause allergic reactions in consumers, and chemical compounds can build up in the body. Previous studies on food colors have focused primarily on synthetic and chemical colors, their stability, metabolism and toxicity, but recent attention has been directed to the biochemical aspects of plant-derived food colors and studies of their utilization. One of the plants that can be used as a dye was the Telang flower. Telang flower (Clitoria ternatea L.) was a flower that has the potential to be an alternative natural food coloring agent in an effort to minimize the use of synthetic dyes and has antioxidant compounds that are beneficial to the body. This study aims to determine the amount of use of butterfly pea flower extract, to analyze the effect of different treatments with the addition of carrageenan and lemon on antioxidant activity and physical properties (viscosity and color). Jelly drink from butterfly pea flower extract in this study used a factorial completely randomized design (RALF) with three levels each. The first factor is carrageenan (0.25%, 0.50%, 0.75%) and the second factor is lemon concentration (1%, 2%, and 3%). Each treatment was repeated 3 times. The results of this study indicate that the difference in the use of the addition of carrageenan: lemon has a significant effect on antioxidant activity, viscosity, and color of jelly drink with telang flower juice. It can be concluded that the higher the concentration of carrageenan and lemon, the higher the antioxidant activity and viscosity produced, and the use of lemon and carrageenan can affect the physical properties of the Jelly drink product with butterfly pea flower juice.